Novel Re(I) tricarbonyl coordination compounds based on 2-pyridyl-1,2,3-triazole derivatives bearing a 4-amino-substituted benzenesulfonamide arm: synthesis, crystal structure, computational studies and inhibitory activity against carbonic anhydrase I, II, and IX isoforms† - Yassine Aimene; Romain Eychenne; Sonia Mallet-Ladeira; Nathalie Saffon; Jean-Yves Winum; Alessio Nocentini; Claudiu T. Supuran; Eric Benoist; Achour Seridi (Taylor & Francis Group, 2019)
In this work, two bidentate 2-pyridyl-1,2,3-triazole ligands (3a and 3b) containing a 4-substituted benzenesulfonamide pharmacophore prepared by classical click chemistry procedures, as well as their corresponding rhenium complexes, 4a and 4b of general formula [ReCl(CO)3(L)] (L = 3a or 3b) were prepared and fully characterised by spectroscopic methods (IR, NMR, MS, UV-Vis), elemental analysis, X-ray diffraction, and theoretical studies using DFT and TD-DFT methods. In particular, we showed that, in the solid state, the pyridine and the triazole rings of 3b adopted an uncommon cis configuration which stems from intermolecular hydrogen bonds. Preliminary assays demonstrated a promising nanomolar inhibitory activity against carbonic anhydrase isoform IX for both ligands and complexes with a strong affinity Ki of 2.8 nM for ligand 3a. More interestingly, complex 4b exhibited a pronounced selectivity against hCA IX over the off-targets hCA I and hCA II which makes this compound a promising potential anticancer drug candidate.